Changing Gender Norms in Islam Between Reason and Revelation - Bakhshizadeh, Marziyeh (Verlag Barbara Budrich, 2018)
Women's movements in Islamic countries have had a long and arduous journey in their quest for the realization of human rights and genuine equality. The author examines whether discriminatory laws against women do in fact originate from Islam and, ultimately, if there is any interpretation of Islam compatible with gender equality. She investigates women's rights in Iran since the 1979 Revolution from the perspectives of the main currents of Islamic thought, fundamentalists, reformists, and seculars, using a sociological explanation.